Epidemiology of Work-Related Injuries Among Construction Workers of Ilam (Western Iran) During 2006 - 2009 - Moradinazar, Mehdi (Kowsar, 2013)
BACKGROUND: Work-related injuries are the most important cause of work absence, disability, retirement, mutilation, and even mortality. In Iran a great number of work-related injuries are occurred in construction industry. However, less than 12% of total workers are active in the construction sector. OBJECTIVES: This study aimed to determine the incidence rate of work-related injuries, the type of injuries, and its other determinants among the construction workers of Ilam (Iran). PATIENTS AND METHODS: The participants were the workers and staffs working in the construction activities of Ilam in Western Iran. All the recorded injuries and deaths related to the construction workers of Ilam from 2006-2009 were collected from the Bureau of Labor and Social Affairs and then analyzed by the statistical package of SPSS (version 19, for Windows). RESULTS: During 2006 - 2009 in Ilam, 387workers encountered the building accidents. Their mean age was 34.3 years (SD = 12.4). The average annual incidence of work-related injuries among the workers was 8.2 per 1000 workers. Fracture with 275 cases (71%) was the most common outcome of injuries, and slipping and falling with 77 cases (36%) were the most important events and exposures. The most important factor related to injuries was the lack of surveillance by employers which was also related with the severity of accident-induced injuries (P < 0.004). CONCLUSIONS: Considering the effectiveness of the relevant preventive measures activities such as training the workers as well as using safety tools and more surveillance by employers can decrease the number of work-related injuries among constructive workers.